Analisis Kondisi Fisik Atlet Renang Putri Klub Moyosyaqi Lombok dengan Kondisi Fisik Atlet Renang Putri Jawa Timur - Fitry Nachamory Oemar; Maulidin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
The purpose of this study is to determine the differences in physical conditions between female swimmers from the Moyosyaqi Swimming Club in Lombok and female swimmers from East Java. The results of this study can be used as a basis for evaluating the training program planning for the Moyosyaqi Swimming Club.The methods used in this study include measuring speed through a 30m sprint, assessing leg muscle strength using the Leg Dynamometer test, determining flexibility through the Standing Trunk Flexion test, and evaluating endurance (VO2max) using the MFT (Multilevel Fitness Test). Based on the results of the study, it was concluded that the average sprint speed of female swimmers from the Moyosyaqi Swimming Club in Lombok was 5.26 m/s, classified as